Intermolecular relationships of major surface proteins of Anaplasma marginale. - Vidotto, M C (1994)
Immunization with Anaplasma marginale membranes containing major surface proteins (MSPs) induces protective immunity against clinical disease (N. Tebele, T. C. McGuire, and G. H. Palmer, Infect. Immun. 59:3199-3204, 1991). For use in design of a recombinant antigen subunit vaccine for A. marginale, intermolecular relationships of known A. marginale MSPs were analyzed. Under nonreducing conditions, MSP-2 and MSP-5 occur as multimers. A large (> 300-kDa-molecular-mass), nonreduced protein complex contained MSP-1a linked by disulfide bonds to MSP-1b and by noncovalent bonds to MSP-5. MSP-2 was also noncovalently bound to this complex. The nearest neighbor membrane proteins were identified by cross-linking reactions followed by immunoblotting with anti-MSP antibodies. A cross-linked aggregate retained in the stacking gel contained MSP-1a, MSP-1b, MSP-2, MSP-3, MSP-4, and MSP-5. Collectively, the data indicate that MSP-2 and MSP-5 occur as monomers and disulfide-bonded multimers. The MSP-1 complex occurs as both disulfide-bonded and noncovalently associated MSP-1 and MSP-1b, and MSP-2 and MSP-5 are noncovalently associated with MSP-1. Also, MSP-1, MSP-2, MSP-3, and MSP-4 are nearest neighbors, and MSP-5 is noncovalently associated with this cross-linked complex.